Exploring the multiple effects of butein on adipogenic differentiation, inflammatory responses, and glucose metabolism in cellular models - Masanori Ohmoto; Atene Matsuya; Mika Mouri; Masaya Takemoto; Tohru Daikoku (Food Chemistry Advances)
Obesity is a significant risk factor for the development of type 2 diabetes due to its association with increased oxidative stress and inflammation. This study investigates the potential therapeutic effects of butein, a plant-derived polyphenol used as a dietary supplement, on adipogenic differentiation in 3T3-L1 cells, as well as its effects on inflammation and glucose metabolism in co-cultured 3T3-L1 and RAW264 cells treated with lipopolysaccharide (LPS). While butein did not significantly affect lipid accumulation in adipocytes, it significantly upregulated the mRNA expression of genes involved in adipogenic differentiation. In addition, butein demonstrated the ability to reduce reactive oxygen species levels in adipocytes. In co-culture with LPS-stimulated cells, butein exhibited anti-inflammatory properties by suppressing the expression of pro-inflammatory cytokines. Although its efficacy in reversing LPS-induced glucose metabolism in 3T3-L1 adipocytes was limited, butein significantly inhibited GLUT1 expression in LPS-stimulated RAW264 cells. The effects of butein on adipogenic differentiation, inflammation and glucose metabolism were found to be concentration dependent, suggesting potential protective benefits in co-cultured cell models under LPS stimulation.